High Neuroticism and Low Conscientiousness Are Associated with Interleukin-6 - Sutin, Angelina R. (2009)
BACKGROUND: High Neuroticism and low Conscientiousness are frequently implicated in health-risk behaviors, such as smoking and overeating, as well as health outcomes, including mortality. Their associations with physiological markers of morbidity and mortality, such as inflammation, are less well documented. The present research examines the association between the five major dimensions of personality and interleukin-6 (IL-6), a pro-inflammatory cytokine often elevated in patients with chronic morbidity and frailty. METHODS: A population-based sample (N=4,923) from four towns in Sardinia, Italy, had their levels of IL-6 measured and completed a comprehensive personality questionnaire, the NEO-PI-R. Analyses controlled for factors known to have an effect on IL-6: age, sex, smoking, weight, aspirin use, and disease burden. RESULTS: High Neuroticism and low Conscientiousness were both associated with higher levels of IL-6. The findings remained significant after controlling for the relevant covariates. Similar results were found for C-reactive protein, a related marker of chronic inflammation. Further, smoking and weight partially mediated the association between impulsivity-related traits and higher IL-6 levels. Finally, logistic regressions revealed that participants either in the top 10% of the distribution of Neuroticism or the bottom 10% of Conscientiousness had an approximately 40% greater risk of exceeding clinically-relevant thresholds of IL-6. CONCLUSIONS: Consistent with the literature on personality and self-reported health, individuals high on Neuroticism or low on Conscientiousness show elevated levels of this inflammatory cytokine. Identifying critical medical biomarkers associated with personality may help to elucidate the physiological mechanisms responsible for the observed connections between personality traits and physical health.